Fibroblast growth factor and canonical WNT/β-catenin signaling cooperate in suppression of chondrocyte differentiation in experimental models of FGFR signaling in cartilage - Buchtová, Marcela; Oralova, Veronika; Aklian, Anie; Masek, Jan; Veselá, Ivana; Ouyang, Zhufeng; Obadalova, Tereza; Konecna, Zaneta; Spoustova, Tereza; Pospisilova, Tereza; Matula, Petr; Varecha, Miroslav; et al. (Biochimica et biophysica acta, 2015)
Aberrant fibroblast growth factor (FGF) signaling disturbs chondrocyte differentiation in skeletal dysplasia, but the mechanisms underlying this process remain unclear. Recently, FGF was found to activate canonical WNT/β-catenin pathway in chondrocytes via Erk MAP kinase-mediated phosphorylation of WNT co-receptor Lrp6. Here, we explore the cellular consequences of such a signaling interaction. WNT enhanced the FGF-mediated suppression of chondrocyte differentiation in mouse limb bud micromass and limb organ cultures, leading to inhibition of cartilage nodule formation in micromass cultures, and suppression of growth in cultured limbs. Simultaneous activation of the FGF and WNT/β-catenin pathways resulted in loss of chondrocyte extracellular matrix, expression of genes typical for mineralized tissues and alteration of cellular shape. WNT enhanced the FGF-mediated downregulation of chondrocyte proteoglycan and collagen extracellular matrix via inhibition of matrix synthesis and induction of proteinases involved in matrix degradation. Expression of genes regulating RhoA GTPase pathway was induced by FGF in cooperation with WNT, and inhibition of the RhoA signaling rescued the FGF/WNT-mediated changes in chondrocyte cellular shape. Our results suggest that aberrant FGF signaling cooperates with WNT/β-catenin in suppression of chondrocyte differentiation.
Keywords: Microscopy, Confocal; HEK293 buňky; Drug Synergism; Signal Transduction; Blotting, Western; protein Wnt3A; Reverse Transcriptase Polymerase Chain Reaction; Cells, Cultured; HEK293 Cells; Humans; chrupavka; Receptors, Fibroblast Growth Factor; Cell Differentiation; Wnt Proteins; nádorové buněčné linie; zvířata; Rats; Models, Biological; synergismus léků; Fibroblast Growth Factors; signální transdukce; beta Catenin; biologické modely; konfokální mikroskopie; chondrocyty; receptory fibroblastových růstových faktorů; polymerázová řetězová reakce s reverzní transkripcí; transkriptom; Limb Buds; Cartilage; Wnt3A Protein; LDL receptor related protein 6; kultivované buňky; fibroblastový růstový faktor 2; krysa rodu Rattus; Animals; končetinové pupeny; Fibroblast Growth Factor 2; proteiny Wnt; western blotting; lidé; beta-katenin; Transcriptome; Chondrocytes; Cell Line, Tumor; buněčná diferenciace; Low Density Lipoprotein Receptor-Related Protein-6; fibroblastové růstové faktory